An investigation into the CuX/2,2 '-bipyridine (X = Br or Cl) mediated atom transfer radical polymerization of acrylonitrile - Matyjaszewski, K; Jo, SM; Paik, HJ; Shipp, DA (AMER CHEMICAL SOC, 1999)
Atom transfer radical polymerization has been used to successfully synthesize polyacrylonitrile (PAN) with predictable molecular weights and narrow polydispersities. This was achieved by using CuX/2,2'-bipyridine (X = Br or Cl) as the catalyst, 2-halopropionitriles as initiators, and ethylene carbonate as a solvent. Monomer consumption showed significant curvature in the first-order kinetic plot, indicating termination is present. H-1 NMR spectroscopy showed that the halide end group is irreversibly removed during the polymerization. Possible reasons for this reaction are given, with the most probable being the reduction of the radical by (CuX)-X-I to form an anion that subsequently deactivates very quickly. Such side reactions limit the molecular weight achievable to M-n < 30 000 while still keeping low polydispersity, M-w/M-n < 1.5.
Keywords: ANIONIC-POLYMERIZATION; POLYACRYLONITRILE